SYNTHESIS AND STUDY OF COMPLEX COMPOUNDS OF 3-AMINO 1,2,4-TRIAZOLE WITH SALTS OF Co (II), Ni (II) AND Cu (II) (Scientific journal of the Fergana State University, 2023)
Methods for the synthesis of complex compounds of 3-amino-1,2,4-triazole with Co (II), Ni (II) and Cu (II) salts have been developed, and the composition and structure of the synthesized complex compounds have been studied using modern physicochemical research methods. It was established that in complex formation reactions the 3-amino-1,2,4-triazole ligand is coordinated through the fourth nitrogen atom of the triazole ring.